2020
DOI: 10.1002/nbm.4407
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of quantitative MRI of extra‐ocular muscles in myasthenia gravis and Graves' orbitopathy

Abstract: Although quantitative MRI can be instrumental in the diagnosis and assessment of disease progression in orbital diseases involving the extra‐ocular muscles (EOM), acquisition can be challenging as EOM are small and prone to eye‐motion artefacts. We explored the feasibility of assessing fat fractions (FF), muscle volumes and water T2 (T2 water ) of EOM in healthy controls (HC), myasthenia gravis (MG) and Graves' orbitopathy (GO) patients. FF, EOM volumes and T2 water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 54 publications
0
42
1
1
Order By: Relevance
“…Studies have found that the fat fraction of skeletal muscle (thigh or calf) in healthy people was ranged from 2 to 5% [ 26 , 27 ], and our fat fraction value of NP group just belonged to the range that described above. Recently, keene et al [ 17 ] reported on the temporal muscle, which is also a masticatory muscle, with a fat fraction of 9.3%, slightly higher than the fat fraction of LPM (ranged from 3.65% to 4.63%) we observed in this study. The closer to the orbital fat, the more noise bias is likely to occur in the imaging of nearby muscles, and resulting in an overestimation of fat fraction.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Studies have found that the fat fraction of skeletal muscle (thigh or calf) in healthy people was ranged from 2 to 5% [ 26 , 27 ], and our fat fraction value of NP group just belonged to the range that described above. Recently, keene et al [ 17 ] reported on the temporal muscle, which is also a masticatory muscle, with a fat fraction of 9.3%, slightly higher than the fat fraction of LPM (ranged from 3.65% to 4.63%) we observed in this study. The closer to the orbital fat, the more noise bias is likely to occur in the imaging of nearby muscles, and resulting in an overestimation of fat fraction.…”
Section: Discussioncontrasting
confidence: 50%
“…The head has rich tissue-air interfaces, which would cause magnetic field inhomogeneity and thus affecting the imaging quality in conventional MRI [ 15 ]. Owing to its short acquisition time and low sensitivity to susceptibility, Dixon-based method is very suitable for head muscle imaging and has been applied preliminary in recent years [ 15 17 ]. Latest literature showed that Dixon-based sequence presented better image quality for extraocular muscles [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicate fat replacement in the EOMs in the early phase of the disease. 6 Moreover, muscle atrophy also extends beyond the EOMs. There was MRI evidence of early muscle atrophy in anti-AChR-Ab MG in the posterior cervical, paraspinal, sternocleidomastoid, and masseter muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising approach is to perform a quantitative analysis of the MRI. It provides quantitative data, such as fat fractions, muscle volumes, and water T2 value for assessing extraocular muscle inflammation, or diameter and crosssectional area of the optic nerve and its sheath, water fraction of the optic nerve, and volume of the fluid in the optic nerve sheath for assessing optic neuropathy [10]. All these quantitative data might be used as biomarkers to diagnose and follow up extraocular muscle inflammation or optic neuropathy in TED.…”
mentioning
confidence: 99%